Needle-in-Needle Technique for Percutaneous Retrieval of a Fractured Biopsy Needle during CT-Guided Biopsy of the Thoracic Spine - Shaikh, Hamza (Interv Neuroradiol, 2014)
Common complications related to CT-guided percutaneous thoracic bone biopsy procedures include pneumothorax and muscular hematoma. Serious, but rare complications include paralysis, nerve injury, CSF leak, and aortic injury. Device failure has not been well documented in the literature. We discuss our experience with biopsy needle breakage during retrieval of a core specimen and the technique used to help retrieve an embedded needle using a CT fluoroscopic-guided, needle-in-needle approach. A 43 year-old man with Stage IIIa NSCLC was found to have a T11 vertebral body lesion as seen on PET, CT, and MR imaging. The patient underwent a CT-guided biopsy in the prone position. The T11 vertebral body was localized and cannulated using the percutaneous Bonopty(®) (Apriomed, Upsala, Sweden) needle device. After fine needle aspiration samples were obtained, a core needle biopsy was attempted with a 16-gauge device. The needle fractured 4 cm deep to the skin during removal of a sclerotic lesion, leaving a retained portion within the pedicle and vertebral body. Using CT-guided fluoroscopy, a large diameter Murphy M2 needle was advanced over the distal portion of the fractured Bonopty needle. The Murphy M2 needle was advanced distal to the tip of the Bonopty needle and removed, capturing the broken Bonopty penetration needle along with a core specimen. Larger-bore biopsy needle systems and/or a coaxial system should be used to perform core biopsies in sclerotic lesions to prevent device fracture. If there is device fracture, a larger-bore needle may be used to help capture the fractured needle and prevent open surgery.